Simulation of implant fitting in the femur bone - Sankupellay, Mangalam; Narainasamy, Selvanathan; Nadia binti Mohd. Ismail, (Sunway University College, 2005)
This research aims to simulate implant-fitting procedures in the human femoral anatomy. Three-dimensional models of the femur and metal femoral implants are used to build a custom-fitted implant model, with the aim of benefiting medical practitioners and patients.